INFECTION OF AGRICULTURAL ANIMALS IN THE NORTHEASTERN REGION OF UZBEKISTAN BY TICKS OF THE GENUS RHIPICEPHALUS (British Journal of Global Ecology and Sustainable Development, 2023)
In the Tashkent and Syrdarya regions, the following species of Rhipicephalus ticks were found: R. sanguineus, R. turanicus, R. bursa, R. pumilio species, a wide distribution of R. sanguineus species in domestic animals was noted. In particular, the damage rate (IE) of agricultural animals was: Bos taurus 38%, Ovis aries 50.6%, Capra hircus 41.8%, Equus caballus 38.1%, Canis lupus familiaris 54.5%.